Logics of Freedom: Debating Religious Freedom Laws and Gay and Lesbian Rights. (28th February 2018) - Kazyak, Emily; Burke, Kelsy; Stange, Mathew
In the wake of marriage equality for same-sex couples, many states have introduced and passed laws that provide religious exemptions for certain services and benefits for LGBTQ (lesbian, gay, bisexual, transgender, and queer) persons. The authors use data from a general population survey of Nebraskans as a mixed-methods case study to examine public opinion of religious freedom laws. Drawing on data from both closed-ended ( n = 1, 117) and open-ended ( n = 838) questions, the authors show that opposition to religious freedom laws is quite high, as 64 percent of respondents report that they oppose laws that would allow business owners to deny services to gay men and lesbians. The authors outline how both sides rely on frameworks that are foundational to the American experience: the protection of rights and the capitalist economy. The authors argue that these appeals to broad American values underscore why these bills will continue to be introduced and seen as controversial despite low levels of support.